Investigating The Role of Job Crafting as Mediator In-between Pro-active Personality and Person-Environment—Fit - Shah, Syed Adnan Ali; Khail, Shahid Jan Kaka (Pakistan Journal of Humanities and Social Sciences, 2023)
In this study, we will examine how to determine the first order of person-environment fit and its components using a hierarchical component model (HCM). The study's overarching goal is to learn how job crafting might facilitate long-term improvements in key dimensions of environmental fit (job fit, group fit, supervisor fit, and vocation fit) among individuals. In addition, our investigation has found a direct and indirect connection between proactive characters and the settings in which they flourish. The theory of labor market demand and supply was used to inform the construction of a conceptual model. We have developed four theories as a result of this. Because of the interconnected nature of these issues, a quantitative study was designed to collect first-hand information from 296 nurses at six public sector hospitals, or MTIs, in the city of Peshawar. The research was structured according to the tenets of positivism and the method of deduction. Questionnaires were sent to nurses in this research using a technique called proportionate random sampling. SPSS was used to do preliminary data screening based on the collected information. Then, structural equation modelling (SEM-PLS) was employed to go even further into the data and put our assumptions to the test. In light of these results, it is clear that the function of job crafting plays a vital role in mediating the association amongst a person's positive personality with the satisfaction in their current position. The conceptual model of the research demonstrates the significance of an independent variable known as proactive personality in each nurse working in the hospital. In addition to this, the results of this research show that job crafting and customization play a significant role as mediators to explain more about how well a person fits into their environment. The present research study has been successful in accomplishing its objectives, but it has also revealed a number of limitations, including time constraints, a restricted population, and a lack of financial resources. In addition, the research has significant repercussions for the academic world, particularly in the medical field. In addition, people in the health care industry, such as nurses, need to take into consideration their proactive personalities in order to improve work by creating actions that are geared towards person-environment fit.